Tofogliflozin attenuates renal lipid deposition and inflammation via PPARα upregulation mediated by miR-21a impairment in diet-induced steatohepatitic mice - Sae Nishihara; Masahiro Koseki; Katsunao Tanaka; Takashi Omatsu; Ayami Saga; Hiroshi Sawabe; Hiroyasu Inui; Takeshi Okada; Tohru Ohama; Daisuke Okuzaki; Yoshihiro Kamada; Masafumi Ono; et al. (Endocrine Journal)
We previously demonstrated hepatic, cardiac, and skin inflammation in a high-fat diet-induced steatotic liver disease (SLD) model. However, the molecular mechanism in the kidneys in this model remains unclear. It has been recently reported that SGLT2 inhibitors improve chronic kidney disease (CKD). Therefore, we used this model to evaluate the effects of tofogliflozin on renal lipid metabolism and inflammation. Male 8–10-week-old C57Bl/6 mice were fed a high-fat/high-cholesterol/high-sucrose/bile acid (HF/HC/HS/BA) diet with 0.015% tofogliflozin (Tofo group) or an HF/HC/HS/BA diet alone (SLD group). After eight weeks, serum lipid profiles, histology, lipid content, and mRNA/microRNA and protein expression levels in the kidney were examined. The Tofo group showed significant reductions in body (26.9 ± 0.9 vs. 24.5 ± 1.0 g; p < 0.001) and kidney weight compared to those of the SLD group. Renal cholesterol (9.1 ± 1.6 vs. 7.5 ± 0.7 mg/g; p < 0.05) and non-esterified fatty acid (NEFA) (12.0 ± 3.0 vs. 8.4 ± 1.5 μEq/g; p < 0.01) were significantly decreased in the Tofo group. Transmission electron microscopy revealed the presence of fewer lipid droplets. mRNA sequencing analysis revealed that fatty acid metabolism-related genes were upregulated and NFκB signaling pathway-related genes were downregulated in the Tofo group. MicroRNA sequencing analysis indicated that miR-21a was downregulated and miR-204 was upregulated in the Tofo group. Notably, the expression of PPARα, which has been known to be negatively regulated by miR-21, was significantly increased, leading to enhancing β-oxidation genes, Acox1 and Cpt1 in the Tofo group. Tofogliflozin decreased renal cholesterol and NEFA levels and improved inflammation through the regulation of PPARα and miR-21a.